Analisis Penyebab Getaran pada Mesin Peniris Minyak untuk Mencegah Kerusakan Produk Keripik Bayam Milik UMKM Jabal Dinar - Maulana, Adam; Ariyanto, Ariyanto; Yudo, Eko (Jurnal Inovasi Teknologi Terapan, 2025)
The oil-draining machine of UMKM Jabal Dinar experienced excessive vibrations, resulting in damage to spinach chips products and ceasing its operations for approximately ±4 years. This study aims to identify the primary causes of unstable vibrations, their impact on product quality, and modification solutions to enhance machine stability. The experimental method was applied through initial vibration measurements, alignment analysis, and evaluation of components such as shafts, bearings, and pulleys. Initial measurements showed vibrations reaching 56.6 mm/s, categorized as Zone D (hazardous) according to the ISO 10816-3 standard. Modifications were made by replacing bent shafts, worn-out bearings, and damaged pulleys. Post-modification results showed a significant reduction in vibration levels, improving machine stability, product quality, and exten.